Improving the energy efficiency of the explosive pulse during drilling and blasting operations to increase the quality of crushing and conditions for conveyor delivery of overburden rocks in quarries and sections - Igbaev, T.M.; Daniyarov, N.A.; Kelisbekov, A.K.; Akashev, A.Z. (Communications, 2025)
Widespread application of advanced transportation technologies in conditions of open-pit mining with the use of high-capacity belt conveyors is limited by the need for additional crushing of overburden rocks and minerals. Accordingly, the quality of crushing of rock mass, the output of oversize during drilling and blasting operations at quarries and open-pit operations significantly affect the possibility of using flow and cyclic-flow technologies with the use of conveyor transport. In this paper is presented a method of increasing the energy efficiency of the explosive pulse in drilling and blasting operations by means of developed gas pedal designs to improve the quality of crushing and conditions of conveyor delivery of rock mass.
Keywords: open-pit mining; cyclic-in-line technologies; conveyor transport; overburden; crushing of rock mass; accelerators; blast wave pulse